If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 3(x + 2) = 5 Reorder the terms: 2 + 3(2 + x) = 5 2 + (2 * 3 + x * 3) = 5 2 + (6 + 3x) = 5 Combine like terms: 2 + 6 = 8 8 + 3x = 5 Solving 8 + 3x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 3x = 5 + -8 Combine like terms: 8 + -8 = 0 0 + 3x = 5 + -8 3x = 5 + -8 Combine like terms: 5 + -8 = -3 3x = -3 Divide each side by '3'. x = -1 Simplifying x = -1
| 1.8=vi+1.5(2.5) | | 7-x/11=0 | | n+2=31 | | 6n+4=6 | | 4y-5+5=24 | | x=23/-9 | | 3(v+6)=-3(6v-7)+6v | | 6x-8+5=13x-4+9 | | 24+.16n=40 | | -11v-10v+14v-14v=14 | | 7n-13=13n-15 | | 2Ln(x)+Ln(x-1)=Ln(-2x^2+5x-3) | | -4w-4(5x-5w)+3x= | | X^2-32x+225=0 | | y=50x+1.50 | | 2u-2+2(4u+2)=-2(u+6) | | 15x+-11x+-7x=18 | | 3r-18=2r-12 | | -3a-1=7a | | 6timesd+136=400 | | 1ab+2bc-7ac=10 | | -2x+34=x+16 | | -3(t+5)=-36 | | 12(23x+46y)+23=762 | | 5t^2-13t-2=0 | | 20x/24 | | x^3+25x-3=0 | | -x-29=4x+11 | | 17t-3t+8t+17t=-11 | | 36+x=4(6+x) | | 1a+2b+3c=4d | | 4a+6=2a-10 |